Earth as an Exoplanet: Investigating the Effects of Cloud Variability on the Direct-imaging of Atmospheres - Soumil Kelkar; Prabal Saxena; Ravi Kopparapu; Joy Monteiro (The Planetary Science Journal)
A planet’s spectrum is dynamic and only represents a time-dependent snapshot of its properties. Changing atmospheric conditions due to climate and weather patterns, particularly variation in cloud cover, can significantly affect the spectrum in ways that complicate the understanding of a planet’s baseline atmospheric properties. Variable cloud cover and cloud properties affect the detectability of atmospheric constituents, and also greatly influence the radiative transfer that determines a planet’s spectrum. This has considerable implications for direct-imaging observations of potentially habitable exoplanets, and thus, it is critical to study and characterize the effects of clouds on their spectra. Clouds have been extensively modeled before, and their effects have been incorporated across climate frameworks spanning a spectrum of complexity. Given the challenges associated with modeling clouds, we adopt a novel approach in this work to study the effects of clouds by using real-time cloud data from Earth observations. Treating Earth as an exoplanet and using detailed observations from the MERRA-2 data collection, we quantify the effects of cloud variability on the spectrum as well as on the detectability of atmospheric constituents, specifically biomarkers like O _2 , O _3 , and H _2 O. The coverage and vertical position of clouds significantly affect the signal-to-noise ratios of these gases and subsequently their detectability in exo-Earth atmospheres. Moreover, we show that variations in the amount of cloud cover will potentially confound efforts to retrieve a stable baseline atmosphere for a planet. This work has important applications to future direct-imaging missions like the Habitable Worlds Observatory.